Anatomy of the Scaphotrapezial Ligament Complex and its Implications for Distal Scaphoid Resection - Yoshimura, Yukiko; Yokota, Atsushi; Fujino, Keitaro; Kondo, Yoichi; Neo, Masashi; Otsuki, Shuhei (The Journal of hand surgery (American ed.), 2025)
This study aimed to describe the detailed configuration and bony attachment of the scaphotrapezial (ST) ligaments to clarify the risk of postoperative dorsal intercalated segment instability in distal scaphoid resection. Twenty-nine hands from 19 formalin-fixed cadavers (13 men and 6 women) were included. We examined the ST ligaments macroscopically and analyzed the bone morphology using computed tomography images and the location of the ligamentous attachments using a defined coordinate system. Additionally, histological examinations of the ST ligaments were performed using Masson's trichrome and toluidine blue staining. The ST ligament comprised three distinct fascicles-superficial, intermediate, and deep-each attached to individual facets; each fascicle was attached to the scaphoid tuberosity at a height of 6.4 ± 1.2, 4.4 ± 1.1, and 3.3 ± 1.0 mm, respectively, from the most distal point of the articular ridge on the distal scaphoid joint surface. Histologically, the deep fascicle demonstrated characteristics of a capsular ligament. The ST ligament has three fascicles that are separate entities, including the deep fascicle that attaches 3.3 mm from the most distal point of the scaphoid. Our findings suggest that preserving the deep fascicle by limiting bone resection to no more than approximately 3 mm at the scaphoid tuberosity during distal scaphoid resection may be important in preventing postoperative dorsal intercalated segment instability.